Pelatihan Pengepakan Produk Minyak Kelapa dan Arang Tempurung Kelapa Untuk Meningkatkan Pemberdayaan Ekonomi Produktif di Desa Purwoharjo, Kecamatan Samigaluh, Kabupaten Kulon Progo - Anisa Nurpita (Jurnal Pengabdian dan Pengembangan Masyarakat, 2018)
The title of this Community Service activity is: "Packing Training for Coconut Oil Products and Coconut Shell Charcoal to Improve Productive Economic Empowerment in Purwoharjo Village, Samigaluh District, Kulon Progo Regency. This activity was carried out by conducting training using a plastic press machine. Training on packing coconut oil and coconut charcoal products took place on Saturday, August 19, 2017 in the Purwoharjo Village Hall, Samigaluh District, Kulon Progo Regency, attended by 40 people, consisting of resource persons, lecturers and students. The results that can be achieved from this activity are 1.) Providing product packing expertise to community members who have the ability to produce coconut oil and coconut shell charcoal products in Purwoharjo Village, 2.) Applying product packaging expertise to community members who have the ability to produce coconut oil and coconut shell charcoal products in Purwoharjo Village.